Overwork Among Residents in India: A Medical Resident′s Perspective - Gulrez S Azhar (Journal of Family Medicine and Primary Care, 2012)
This paper argues that medical residents who do most of the hard work in big hospitals and medical colleges are overworked. A hierarchical organizational structure, staffing patterns, and fear of failure in examinations leads to overwork among residents going unreported. This can lead to poor academic performance and research work. Gaps in communication have serious implications on patient health. Undesirable practices like LAMA (leave against medical advice) also result from overwork. Issues of pay and contracts including mandatory service need to be looked into carefully. National and international recommendations on work hours have consistently been ignored. The solutions suggested are simple and easy to implement.